Deregulation and Board Policies: Evidence from Performance and Risk Exposure Measures Used in Bank CEO Turnover Decisions - Hayes, Rachel M.; Tian, Xiaoli; Wang, Xue (The Accounting Review, 2023)
ABSTRACT We examine the effects of banking deregulation on bank board policies—specifically, whether deregulation affects the performance and risk exposure measures used in bank CEO turnover decisions. Using the staggered adoption of interstate branching as our setting, we find that bank CEO turnover is more (less) sensitive to stock (accounting) performance after deregulation. We also find that deregulation is associated with a higher sensitivity of bank CEO turnover to the idiosyncratic component of tail risk. Moreover, such changes in turnover policies primarily exist in large banks and federally chartered banks, which are best positioned to exploit growth opportunities, and in banks that expand branch operations after deregulation. Our results indicate an increased emphasis on stock performance and tail risk in turnover decisions when growth opportunities are greater in the deregulated environment. The findings provide evidence that the information used in board decisions varies with features of the competitive environment.